CPC-013 Analysis of Antifungal Use and Cost in a Specialist Hospital During the Last Three Years (2009–2011). (12th March 2013) - de Travecedo, MT Gomez; Almendral, A; Gavira, R; Gomez, P; Lobato, M; Gonzalez, R; Moreno, MT; Gomez, F; Gazquez, R; Diaz, JP
Abstract : Background: Although antifungals constitute a small part of the antimicrobial drugs used in hospitals, proportionally their cost is high. Therefore, the use of antifungal analysis is important in order to achieve optimal clinical outcomes by appropriate management of resources. Purpose: To analyse antifungal use and cost in a specialty hospital over the last three years (2009–2011). Materials and Methods: Antifungal consumption was analysed in economic terms and number of Defined Daily Doses (DDDs). Data was processed for the whole hospital and broken down by clinical unit. WHO-ATC/DDD Index 2012 was used for DDDs calculations. Results were expressed in DDD/100 Stay-days (DDDs/100SD). Stay-days data were obtained from hospital healthcare activity records. Use data collected were: J02AA-antibiotics antimycotics for systemic use, J02AC-triazole antimycotics for systemic use, and J02AX-other antimycotics for systemic use. Consumption values were extracted from the pharmacy management SINFHOS computer application. DDDs automatically were calculation was made using EDUS_SUR application. Results: During last three years, antifungal use expressed in DDDs/100SD was 6.72% of anti-infective drugs used. The cost of antifungals represented 43.59% of the total cost of antimicrobials. 85% DDDs were prescribed by Haematology (105.55 DDDs/100SD), Intensive Care (43.38 DDDs/100SD), Infectious Diseases (12.49 DDDs/100SD), and Oncology (5.92 DDDs/100SD). Antifungal use went up especially in Infectious Diseases, which increased from 7.74 DDDs/100SD in 2009 to 21.72 DDDs/100SD in 2011. Of the antifungal agents, the most prescribed were fluconazole (10.46 DDDs/100SD) and amphotericin B (6, 00 DDDs/100SD), followed by voriconazole (1.36 DDDs/100SD) and caspofungin (1.35 DDDs/100SD). The selection of antifungals evolved: fluconazole use increased from 1.31 to 3.71 DDDs/100SD, and amphotericin-B use increased from 1.31 to 2.90 DDDs/100SD, while caspofungin use decreased from 0.63 to 0.33 DDDs/100SD. Conclusions: The cost of systemic antifungals represents nearly half of anti-infective drugs expenditure in our hospital. Efforts to assure optimal use of antifungals must be reinforced In Haematology, Intensive Care, Infectious and Oncology, by proposing clinical guides or protocols for prophylactic and treatment use. No conflict of interest.